2003
DOI: 10.2514/2.1895
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Experiment of Gas Leakage Through Composite Laminates for Propellant Tanks

Abstract: The mechanism of the through-thickness gas leakage of carbon ber-reinforced plastics (CFRP) laminates is investigated in view of propellant leaks for composite tanks of reusable launch vehicles. In this study analysis of leakage caused by the existence of matrix cracks acting as the chain of leakage paths is developed under the simple assumption that conductance for leakage is a function of crack-opening displacements. The analytical results in consideration of mechanical and thermal loads are compared with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 5 publications
0
59
0
Order By: Relevance
“…However, increasing rate of permeability in connection with the strains was dominated by crack opening displacements, which were controlled by the external biaxial loads and were nearly independent of the crack densities when the crack intervals were sufficiently large compared with the thickness of layers. The leak analysis developed by Kumazawa et al [11] indicated that matrix crack densities and crack opening displacements effect quantity of permeability with an unloaded state and increasing rate of permeability under biaxial loadings, respectively, when the crack densities are adequately small. Comparing the permeability of the specimens C2 and A2 in Fig.…”
Section: Effect Of Stacking Sequences On Damage and Leakage Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing rate of permeability in connection with the strains was dominated by crack opening displacements, which were controlled by the external biaxial loads and were nearly independent of the crack densities when the crack intervals were sufficiently large compared with the thickness of layers. The leak analysis developed by Kumazawa et al [11] indicated that matrix crack densities and crack opening displacements effect quantity of permeability with an unloaded state and increasing rate of permeability under biaxial loadings, respectively, when the crack densities are adequately small. Comparing the permeability of the specimens C2 and A2 in Fig.…”
Section: Effect Of Stacking Sequences On Damage and Leakage Propertiesmentioning
confidence: 99%
“…The leakage through composite laminates under mechanical loads and cryogenic condition was experimentally investigated [8,9], and permeability through the damaged laminate changes with not only temperature variation but also with applied loads. Leakage analysis scheme was also developed in consideration of the relationships between damage and gas permeation, and good agreement with experimental data were shown [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Subscripts 1 and 2 respectively denote the CFRP (0° or 90°) and GM. The CTE and elastic moduli of CFRP are, respectively, -0.5 × 10 -6 K -1 and 153 GPa for the 0 direction, and 22 × 10 -6 K -1 and 8.2 GPa for the 90° direction [6].…”
Section: Introductionmentioning
confidence: 97%
“…An important issue related to cryogenic composite tanks is gas leakage that occurs through microscopic damage such as matrix cracks, fiber/matrix debonding, and delamination [6][7][8][9][10]. Matrix crack propagation occurs from low tensile strain (0.2-0.5%) at cryogenic temperatures compared with room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…microcracking, delamination) [2][3][4] owing to thermo-mechanical loadings and foreign object impacts during operation, characterization of microscopic damages is significantly important for composite tank structures. In addition, the accumulation of these microscopic damages, which are, in general, barely visible, might induce severe propellant leakage resulting in a serious threat to the vehicle 5) , especially if a tank is to be unlined.…”
Section: Introductionmentioning
confidence: 99%